Radial symmetry - Larson, Katherine, 1977- (Yale series of younger poets, 2011)
Katherine Larson is the winner of the 2010 Yale Series of Younger Poets Competition. With Radial Symmetry, she has created a transcendent body of poems that flourish in the liminal spaces that separate scientific inquiry from empathic knowledge, astute observation from sublime witness. Larson's inventive lyrics lead the reader through vertiginous landscapes--geographical, phenomenological, psychological--while always remaining attendant to the speaker's own fragile, creaturely self. An experienced research scientist and field ecologist, Larson dazzles with these sensuous and sophisticated poems, grappling with the powers of poetic imagination as well as the frightful realization of the human capacity for ecological destruction. The result is a profoundly moving collection: eloquent in its lament and celebration. Metamorphosis [excerpt]We dredge the stream with soup strainersand separate dragonfly and damselfly nymphs-their eyes like inky bulbs, jaws snappingat the light as if the world was full oftiny traps, each hairpin mechanismtripped for transformation. Such a ricochetof appetites insisting life, life, life againstthe watery dark, the tuberous reeds.